ILM AL DALALAH WA DAURUHU FI FAHM AL NUSHUSH AL ARABIYYAH - Muhamad Jaeni (Arabic Education Program IAIN Pekalongan, 2016)
One of the most difficult things in learning Arabic language is understanding the structure of the text. It may caused by the complication of its structure and also the complex meaning of each word. Consequently, knowing the meaning of a word is very important in understanding an Arabic language text. Therefore, there is a branch of Arabic language which specifically discusses about meaning, called semantics. One of the discussions is about the field of meaning such as synonym, antonym, polysemy, etc. They have important role in understanding sentence structure of a text. Therefore, learning semantics is an obligation for those who want to be able to understand Arabic language text well.